3(y+2)-2=2(4-y)

Simple and best practice solution for 3(y+2)-2=2(4-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y+2)-2=2(4-y) equation:


Simplifying
3(y + 2) + -2 = 2(4 + -1y)

Reorder the terms:
3(2 + y) + -2 = 2(4 + -1y)
(2 * 3 + y * 3) + -2 = 2(4 + -1y)
(6 + 3y) + -2 = 2(4 + -1y)

Reorder the terms:
6 + -2 + 3y = 2(4 + -1y)

Combine like terms: 6 + -2 = 4
4 + 3y = 2(4 + -1y)
4 + 3y = (4 * 2 + -1y * 2)
4 + 3y = (8 + -2y)

Solving
4 + 3y = 8 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
4 + 3y + 2y = 8 + -2y + 2y

Combine like terms: 3y + 2y = 5y
4 + 5y = 8 + -2y + 2y

Combine like terms: -2y + 2y = 0
4 + 5y = 8 + 0
4 + 5y = 8

Add '-4' to each side of the equation.
4 + -4 + 5y = 8 + -4

Combine like terms: 4 + -4 = 0
0 + 5y = 8 + -4
5y = 8 + -4

Combine like terms: 8 + -4 = 4
5y = 4

Divide each side by '5'.
y = 0.8

Simplifying
y = 0.8

See similar equations:

| 3(y+2)-2=2(41y) | | 5s-19s=28 | | 4t+3=t-18 | | 8+2x*3=x*4+12 | | a^2x+3x=2a^2 | | x^2-5.75+7.75=6 | | x^2-5.75+7.75=1 | | x^2-5.75+7.75=4 | | x^2-5.75+7.75=2 | | 2x^2-4x+8.8=2 | | 2x^2-4x+18.2=2 | | 5a^2-6a=1 | | (10b-6)-3(3b+2)=-3 | | x^2-8x+15.75=0 | | y=0(0)-7 | | (4y+9)(4y+9)=64y^3+432y^2+972y+729 | | 5c+6=2-y | | 5x+6x+3+8=3x+5+7x | | 16+-8-9= | | z^2-8z-20= | | 3(Q-6)=2(2Q+7)+10 | | 25+-15-12= | | 15x^2+5x-20= | | y=18(0)+0 | | 9y^2+21y+6= | | 2x+3x=30-z | | y=-7(0)+4 | | 3x^2-4y=20 | | 3x^2-4y=20 | | 5(t-3)+7t=4(3t+3)-10 | | 2x^2+5y^2=30 | | -2(5s-6)-12=-2(7s+2)-3 |

Equations solver categories